2006
DOI: 10.1111/j.1574-6968.1997.tb10347.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ergosterol biosynthesis is not accompanied by a change in fatty acid composition in Saccharomyces cerevisiae treated with the antifungal agent 6-amino-2-n-pentylthiobenzothiazole

Abstract: The antifungal agent 6-amino-2-n-pentylthiobenzothiazole at a concentration of 40 microM lowered the specific growth rate of exponentially growing cultures of Saccharomyces cerevisiae by 36%. Treatment with 6-amino-2-n-pentylthiobenzothiazole inhibited the biosynthesis of ergosterol and caused an accumulation of the methylated sterol precursors ergosta-5,7-dienol and squalene, but had no significant effect on the composition and the rate of biosynthesis of fatty acids. The results indicate that neither the inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…APB has been shown to bind to Erg25p and inhibits its catalytic function in a competitive manner (9,21). The treatment of yeast with APB inhibited the biosynthesis of ergosterol and led to the accumulation of the methylated sterol precursors, such as ergosta-5,7-dienol and squalene, but had no significant effect on the composition and the rate of biosynthesis of fatty acids (22). We found that applying increasing amounts of APB to the growth medium affected both yeast growth and TBSV accumulation ( Fig.…”
Section: Downregulation Of Erg25 Mrna Level In Yeast Reduces Tbsv Rnamentioning
confidence: 99%
“…APB has been shown to bind to Erg25p and inhibits its catalytic function in a competitive manner (9,21). The treatment of yeast with APB inhibited the biosynthesis of ergosterol and led to the accumulation of the methylated sterol precursors, such as ergosta-5,7-dienol and squalene, but had no significant effect on the composition and the rate of biosynthesis of fatty acids (22). We found that applying increasing amounts of APB to the growth medium affected both yeast growth and TBSV accumulation ( Fig.…”
Section: Downregulation Of Erg25 Mrna Level In Yeast Reduces Tbsv Rnamentioning
confidence: 99%
“…41) did not efficiently comply with the criteria of interesting new drug targets [25][26][27][28]. Recently, the characterization of a natural steroidal inhibitor of a sterol-4α-carboxylate-3-dehydrogenase, an enzyme of the sterol-C4-demethylation complex from yeast (C4DMC) clearly indicated that many target enzymes had been overlooked so far in chemical and pharmaceutical screenings for new bioactive ligands [29,30].…”
Section: Introductionmentioning
confidence: 99%